Prednosti in omejitve metode BSC - Hočevar, Marko (Les (Ljubljana), 2003)
In the recent years, with big changes in the environment of business, the meaning of (management) accounting information for management decisions, has increased. In this article, one of the contemporary accounting methods for evaluating of busines performance has been analisied, this method is balanced score card (BSC). The biggest advantage of BSC is that it measures long-term effectivness of firm. Disadvantages of this methods are its noncompleteness and complexity.
Keywords: podjetja; uspešnost poslovanja; modeli; BSC